(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Anaphylactic deaths are a challenge during autopsy due to the minimal autopsy findings. The role of beta tryptase and IgE in the diagnosis of anaphylactic deaths is well established. However, contradicting studies challenge the veracity of these biomarkers as they are found to be raised even in non-anaphylactic deaths. In this study, the postmortem serum Beta Tryptase and IgE levels in various causes of deaths other than anaphylaxis was analyzed to find out its diagnostic significance and relevance in autopsy samples.